2024
DOI: 10.1002/est2.556
|View full text |Cite
|
Sign up to set email alerts
|

Novel design and adaptive coordinated energy management of hybrid fuel‐cells/tidal/wind/PV array energy systems with battery storage for microgrids

Youcef Belkhier,
Adel Oubelaid

Abstract: This paper proposes a comprehensive solution to the challenges of managing a hybrid microgrid that generates electricity from multiple sustainable energy sources by proposing a coordinated energy management strategy and storage system. As renewable energy generation becomes increasingly popular, it introduces greater intermittency and stochasticity in energy management. To address this issue, a coordinated energy management strategy and storage system is proposed, which includes a fuzzy logic modified super tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The physical prototype layout of a 4-terminal DC microgrid has been extended to six terminals (Belkhier and Oubelaid, 2024;Al-Ismail, 2021;Ali et al, 2021;Al sumarmad et al, 2023) in the simulation environment, as shown in Figure 10 above. The ratings of software model has been enlisted in Table 3.…”
Section: Software Implementationmentioning
confidence: 99%
“…The physical prototype layout of a 4-terminal DC microgrid has been extended to six terminals (Belkhier and Oubelaid, 2024;Al-Ismail, 2021;Ali et al, 2021;Al sumarmad et al, 2023) in the simulation environment, as shown in Figure 10 above. The ratings of software model has been enlisted in Table 3.…”
Section: Software Implementationmentioning
confidence: 99%
“…Microgrids can provide an effective solution to the problems of difficult distributed resource management and insufficient power grid regulation capacity caused by new energy access (Ju and Chen, 2023;Belkhier and Oubelaid, 2024). At the same time, demand response guides users to actively shift and avoid peak loads through market-oriented means (Xu et al, 2018;Wang et al, 2020), which effectively reduce peak loads while also obtaining certain economic benefits for users.…”
Section: Introductionmentioning
confidence: 99%